Malawi's challenging employment landscape - Baulch, Bob; Benson, Todd; Erman, Alvina; Lifeyo, Yanjanani; Mkweta, Priscilla (International Food Policy Research Institute, 2019)
Using three rounds of the Integrated Household Survey conducted between 2004 and 2016, this paper examines Malawi’s challenging employment landscape, focusing on its rapidly growing youth. It finds little evidence of a structural transformation in Malawi’s economy or of youth being in the vanguard of any changes in cross-sectoral patterns of employment. Most Malawians spend all of their working years in the agricultural sector – indeed, the share of employment in agriculture in Malawi rose slightly between 2004 and 2016, though the share of full-time jobs inside agriculture declined during this period. Tabular analysis and multivariate modelling of employment choices show that youth are not participating in the limited growth that has occurred in services. Agriculture remains the sector in which most Malawians first obtain employment, and it is only later in their working lives that Malawian workers, particularly males, are in a position to obtain employment outside of agriculture alone. Malawi’s challenging employment landscape for youth is characterized by a scarcity of jobs outside agriculture and insufficient work hours within agriculture.